A School-Community Career Education Project. Final Report - Opelika City Schools, AL.; Opelika City Schools, AL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
The 3-year Opelika City (Alabama) School-Community Career Education Project sought to make career education central and not just an adjunct to the education program in Opelika schools. Development of the project was carried out through four phases: (1) Staff training and development, (2) curriculum development and revisions, (3) guidance, and (4) community coordination. A product-process evaluation strategy was used to assess the progress of the project during the 1975-76 school year. Evaluation showed that the project contributed to the development of a dynamic school system with a high degree of involvement in the curriculum development process by teachers and the community at large. Data reported from scores on the Coopersmith Self-Esteem Inventory, the California Achievements Tests, the Career Maturity Inventory (CMI), and CMI subtests showed that Opelika students scored significantly higher than national norm groups. Changes were also found in teachers' attitudes and skills as they fused career education concepts with regular school curriculum, in teachers' attitudes toward individualized instruction, and in the high degree of community support. Appendixes and attachments contain forms and materials used in the project and include junior and senior high school summer activities, guidelines for career education workshops, request forms, evaluation design for the project, career education questionnaire, and a list of instructional materials. (TA)
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
Contract Number: OEG-0-73-5284.
Educational level discussed: Elementary Secondary Education.
Educational level discussed: Postsecondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Awareness; Career Education; Career Exploration; Career Guidance; Curriculum Development; Elementary Secondary Education; Fused Curriculum; Inservice Teacher Education; Postsecondary Education; Program Descriptions; Program Development; Program Evaluation; School Community Relationship; Staff Development; Teacher Workshops; Alabama; Alabama (Opelika); Reports, Descriptive